Hydrophobic catalyst and preparation method thereof

By loading carbon and active metal layer by layer to the metal framework and performing hydrophobic modification, the existing hydrophobic catalysts have been solved, and a hydrophobic catalyst with high catalytic activity and good hydrophobicity has been achieved.

CN119869552AActive Publication Date: 2025-04-25CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411962518.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In large-scale industrial applications, existing granular hydrophobic catalysts have excessive gas resistance and are prone to "liquid overflow" phenomena, and regular hydrophobic catalysts still have room for improvement in improving catalytic activity and reducing costs.

Method used

By layer-by-layer loading method, the powdered carbon and active metal are loaded onto the metal framework and after the active metal is supported, hydrophobic modification is performed by a modified solution including hydrophobic silane to form a hydrophobic catalyst with improved catalytic activity.

Benefits of technology

The catalytic activity and hydrophobicity of the hydrophobic catalyst are significantly improved, the coverage of the active metal is reduced, the utilization rate of the active metal is improved, and the overall performance of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869552A_ABST
    Figure CN119869552A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophobic catalyst and a preparation method thereof. The preparation method comprises the steps that S1, carbon-containing turbid liquid is attached to a metal framework and then dried, carbon is loaded to the metal framework, a composite carrier is obtained, and the carbon-containing turbid liquid comprises powdery carbon dispersed in silica sol and a dispersing agent; s2, loading active metal onto the composite carrier to obtain an original catalyst; s3, the original catalyst is treated through a modified solution, the hydrophobic catalyst is obtained, and the modified solution comprises hydrophobic silane and an organic solvent. The hydrophobic catalyst has good catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hydrophobic catalysts, and in particular to a hydrophobic catalyst using a metal skeleton as a carrier and a preparation method thereof. Background Art

[0002] With the development of nuclear energy, the treatment of a large amount of tritium-containing wastewater produced by nuclear power plants has become an important topic. Water-hydrogen catalytic exchange reaction is an effective method for achieving hydrogen isotope separation. It has the advantages of high separation factor, low energy consumption, and environmental friendliness. It has a very broad application prospect in the treatment of tritium-containing wastewater. In the process of water-hydrogen catalytic exchange reaction, in order to avoid the active sites being covered by liquid water to cause "water poisoning", a hydrophobic catalyst must be used in the reaction process. At present, hydrophobic catalysts are generally composed of active components and carriers, wherein the carrier is usually styrene-divinylbenzene copolymer (SDB), polytetrafluoroethylene (PTFE) or other inert carriers such as ceramics, mainly in the form of small particles. Granular hydrophobic catalysts have excessive gas resistance and are prone to "liquid flooding" during large-scale industrial applications, while regular hydrophobic catalysts have the advantages of low gas resistance, low cost, and strong mass and heat transfer capabilities, which are more advantageous in large-scale industrial applications. Therefore, it is necessary to provide an improved regular hydrophobic catalyst. Summary of the invention

[0003] In view of this, the main purpose of the present disclosure is to provide a method for preparing a hydrophobic catalyst, which has a simple process and the obtained hydrophobic catalyst has good catalytic activity.

[0004] In order to achieve the above objectives, the present disclosure provides the following technical solutions.

[0005] The first aspect of the present disclosure provides a method for preparing a hydrophobic catalyst, including S1, by attaching a carbonaceous suspension to a metal skeleton and then drying it to load carbon onto the metal skeleton to obtain a composite carrier, wherein the carbonaceous suspension includes powdered carbon and a dispersant dispersed in a silica sol; S2, loading an active metal onto the composite carrier to obtain an original catalyst; and S3, treating the original catalyst with a modified solution to obtain the hydrophobic catalyst, wherein the modified solution includes a hydrophobic silane and an organic solvent. The present disclosure first loads powdered carbon onto a metal skeleton through a silica sol in a layer-by-layer loading manner, and the obtained composite carrier has an increased specific surface area, which is beneficial to the subsequent loading of active substances; and then further loading the active metal, and after loading the active metal, hydrophobic modification is performed by a modified solution including a hydrophobic silane, while achieving hydrophobic modification, the utilization rate of the active metal is improved, thereby improving the catalytic activity of the hydrophobic catalyst.

[0006] According to an embodiment of the present disclosure, the metal skeleton is made of any one of nickel, iron, cobalt, copper, magnesium, aluminum, and stainless steel, which is conducive to selecting the metal skeleton according to the actual purpose to meet the requirements of corrosion resistance, cost, etc.

[0007] According to one embodiment of the present disclosure, the metal skeleton is in the form of any one of foam, wire mesh, fiber, and honeycomb, which is beneficial for regulating the resistance of fluid passing through the catalyst and increasing the specific surface area of ​​the metal skeleton, which is beneficial for the subsequent loading of active substances.

[0008] According to an embodiment of the present disclosure, relative to the total mass of the carbonaceous suspension, the mass percentage of the powdered carbon is 1% to 5%, the mass percentage of the dispersant is 0.5% to 3%, and the mass percentage of silicon dioxide in the silica sol relative to the silica sol is 20% to 40%. This is conducive to forming a stable carbonaceous suspension and achieving uniform adhesion.

[0009] According to an embodiment of the present disclosure, the powdered carbon is selected from one or more of activated carbon, graphite powder, carbon nanotubes, and carbon black, thereby facilitating the increase of the specific surface area of ​​the metal skeleton.

[0010] According to one embodiment of the present disclosure, the average particle size of the powdered carbon is 10 nm to 100 nm, which is beneficial to increase the specific surface area of ​​the metal skeleton.

[0011] According to one embodiment of the present disclosure, the dispersant is Triton X-100, which is beneficial to the stability of the carbonaceous suspension and the formation of a more uniformly dispersed attachment on the metal skeleton.

[0012] According to an embodiment of the present disclosure, in S1, the drying temperature is 100° C. to 120° C. and the drying time is 1 hour to 3 hours, which is conducive to the volatilization of water in the silica sol and the silica particles play a bonding role.

[0013] According to one embodiment of the present disclosure, the mass ratio of the composite carrier to the metal skeleton is (1.2-1.8): 1. This is beneficial to increase the specific surface area of ​​the metal skeleton, increase the sites for subsequent loading of active substances, and improve the dispersibility of the active substances.

[0014] According to one embodiment of the present disclosure, in S2, loading the active metal onto the composite carrier comprises: immersing the composite carrier in a solution comprising ions containing active metal elements, and volatilizing the solvent in the solution comprising ions containing active metal elements to obtain a carrier loaded with an active metal precursor, wherein the active metal is selected from one or more of Pt, Pd, Ru, Rh, Ir, Fe, Fe-doped Pt, Ru-doped Pt, and Ir-doped Pt; and performing a reduction treatment on the carrier loaded with the active metal precursor to obtain an original catalyst, wherein the reduction treatment comprises reducing the carrier loaded with the active metal precursor in an atmosphere containing a reducing gas. The above-mentioned impregnation process utilizes a uniform solution comprising ions containing active metal elements, which is conducive to the attachment of metal ions to the composite carrier. The above-mentioned reduction process using a reducing gas is conducive to sufficient reduction to obtain the active metal.

[0015] According to one embodiment of the present disclosure, the solvent of the solution including ions containing active metal elements is selected from one or more of ethanol, methanol, water, ethylene glycol, and acetone.

[0016] According to one embodiment of the present disclosure, the reducing gas is hydrogen.

[0017] According to an embodiment of the present disclosure, the content of the active metal element in the solution including ions containing the active metal element is 3 g / L to 10 g / L, which is beneficial to improving the catalytic efficiency of the hydrophobic catalyst and has good cost-effectiveness.

[0018] According to one embodiment of the present disclosure, the ratio of the mass of the composite carrier to the volume of the solution including ions containing active metal elements is 0.1 g / mL to 1.0 g / mL.

[0019] According to one embodiment of the present disclosure, in S3, treating the original catalyst with the modifying solution includes drying the modified solution after adhering to the original catalyst, thereby simplifying the process and allowing the original catalyst to fully contact with the modifying solution, thereby facilitating the improvement of hydrophobicity.

[0020] According to one embodiment of the present disclosure, in the modified solution, the organic solvent is ethanol.

[0021] According to one embodiment of the present disclosure, the hydrophobic silane comprises a structural formula of R n SiR' m Silane, n is 1, 2 or 3, m=4-n, R is a C1~C20 alkyl group substituted by fluorine, and R' is a C1~C4 alkoxy group.

[0022] According to an embodiment of the present disclosure, if R has x carbon atoms, R is substituted with 2x-9 to 2x+1 fluorine atoms, thereby being more conducive to improving the hydrophobicity.

[0023] According to an embodiment of the present disclosure, in the modified solution, the mass percentage of the hydrophobic silane is 0.1% to 0.5%, which is conducive to better dispersion of the hydrophobic silane in the organic solvent, so that the hydrophobic silane is evenly attached to the original catalyst.

[0024] According to one embodiment of the present disclosure, before S2, the preparation method further includes: loading the cobalt oxide precursor onto the composite support by a hydrothermal method; and calcining the composite support loaded with the cobalt oxide precursor to obtain a composite support loaded with cobalt oxide, wherein loading the cobalt oxide precursor onto the first support by a hydrothermal method includes reacting an aqueous mixture including the cobalt source, the nickel source, the composite support, a surfactant and a nucleating agent in a hydrothermal reactor, wherein the molar ratio of the cobalt element in the cobalt source to the nickel element in the nickel source is 2: 1. The cobalt oxide can further increase the specific surface area and roughness of the support, which is beneficial to increase the attachment sites for loading active metals in S2, and the cobalt oxide contains abundant hydroxyl groups, which is beneficial to react with hydrophobic silanes in S3 to further improve the hydrophobicity.

[0025] According to an embodiment of the present disclosure, the temperature of the hydrothermal reaction is 110° C. to 130° C., and the time is 5 h to 8 h. This is conducive to the full progress of the hydrothermal reaction and the formation of a nickel cobalt oxide precursor on the composite support.

[0026] According to one embodiment of the present disclosure, the amount of the cobalt element in the cobalt source is 0.1 mmol to 1 mmol per gram of the composite carrier.

[0027] According to one embodiment of the present disclosure, the concentration of ions containing the cobalt element in the cobalt source is 0.01 mol / L to 0.1 mol / L relative to the aqueous mixture.

[0028] According to an embodiment of the present disclosure, the calcination temperature is 300° C. to 450° C. and the calcination time is 2.5 h to 4.5 h, which is beneficial for converting the cobalt oxide precursor into nickel cobalt oxide.

[0029] According to one embodiment of the present disclosure, the surfactant is hexadecyltrimethylammonium bromide.

[0030] According to one embodiment of the present disclosure, the nucleating agent is urea.

[0031] According to one embodiment of the present disclosure, relative to the aqueous mixture, the concentration of the surfactant is 0.005 mol / L to 0.04 mol / L, and the concentration of the nucleating agent is 0.02 mol / L to 0.20 mol / L.

[0032] The second aspect of the present disclosure provides a hydrophobic catalyst obtained by the preparation method described in any one of the above embodiments. The hydrophobic catalyst has improved catalytic activity and the above other advantages.

[0033] The present invention adopts a layer-by-layer loading method, firstly loading powdered carbon onto a metal skeleton through silica sol, which can significantly increase the specific surface area of ​​the metal skeleton and is beneficial to the subsequent loading of active substances; then further loading active metals, increasing the exposure of the active metals and improving the utilization rate of the active metals; and then performing hydrophobic modification through a modification solution including hydrophobic silane to improve the catalytic activity of the hydrophobic catalyst.

[0034] In addition to the technical problems solved by the present disclosure, the technical features that constitute the technical solutions, and the beneficial effects brought about by the technical features of the technical solutions described above, other technical problems that can be solved by the present disclosure, other technical features included in the technical solutions, and the beneficial effects brought about by these technical features will be further described in detail in the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 A scanning electron microscope image of the hydrophobic catalyst of Example 2 is shown.

[0037] Figure 2 A contact angle test graph of the hydrophobic catalyst of Example 2 is shown.

[0038] Figure 3 The curves of the total volume mass transfer coefficient Kya of Examples 1, 2 and Comparative Example 1 with respect to the gas velocity are shown. DETAILED DESCRIPTION

[0039] The technical solution of the present disclosure will be clearly and completely described below in conjunction with specific implementations and drawings. Obviously, the described implementations are only part of the implementations of the present disclosure, not all of the implementations. Based on the implementations in the present disclosure, all other implementations obtained by ordinary technicians in the field without creative work are within the scope of protection of this application.

[0040] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. In the event of a conflict, this specification takes precedence.

[0041] It should be noted that in the present disclosure, the term "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "comprising..." does not exclude the presence of other related elements in the method or device including the element.

[0042] Except in any operating examples, or where otherwise indicated, all numerals used in the specification and claims indicating component amounts, reaction conditions, etc. should be understood to be modified by the term "approximately" in all cases. Unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximate values, which can vary according to the desired properties to be obtained by the present disclosure. Although the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximate values, the numerical values ​​set forth in the specific embodiments are reported as accurately as possible.

[0043] The above steps are divided only for clear description. When implemented, they can be combined into one step or some steps can be split and decomposed into multiple steps. As long as they include the same logical relationship, they are all within the protection scope of this patent.

[0044] Definition of terms

[0045] As used herein, the term "contact angle" refers to the angle between the solid-liquid interface through the liquid interior to the gas-liquid interface at the junction of solid, liquid and gas phases. The size of the contact angle reflects the interaction strength between the liquid and the solid, and is an important parameter for the affinity of the solid surface to the liquid. In this application, the "contact angle" can be directly obtained by dripping a drop of deionized water on the solid surface to be tested through a contact angle meter to test its spreadability. The larger the contact angle, the stronger the hydrophobicity.

[0046] The term "alkyl" includes both branched and straight chain saturated aliphatic hydrocarbon groups and has a specified number of carbon atoms, for example, 1 to 12 carbon atoms. As used herein, the term "C1-C20 alkyl" means an alkyl group having 1 to 20 carbon atoms, such as C1-C18, C1-C10, or C1-C8 alkyl. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, 3-methylbutyl, tert-butyl, n-pentyl, sec-pentyl, hexyl, heptyl, octyl, isooctyl, nonyl, decyl, dodecyl, hexadecyl, and the like.

[0047] Herein, unless otherwise indicated, numerical ranges such as "1 to 20" or "1-20" refer to each integer in the given range; for example, "1 to 20 carbon atoms" means that the alkyl group can be composed of 1 carbon atom, 2 carbon atoms, 3 carbon atoms, etc., up to and including 20 carbon atoms. However, there are some exceptions that are obvious to those skilled in the art. In particular, herein, when a given range is used to express a molar ratio, diameter or size, pH, time period, concentration, osmotic pressure or temperature, the range also includes all decimals falling within the range, including the upper and lower limits.

[0048] In the research reported so far, some hydrophobic catalysts using regular carriers are disclosed, and the carriers are mainly cordierite, foamed nickel (FN), foamed silicon carbide (SiC), etc. Such hydrophobic catalysts have the advantages of regular shape and low gas resistance. The document (Xu M, Zhang S, Wang T, et al. De novo design of a Pt nanocatalyst on a conjugated microporous polymer-coated honeycomb carrier for oxidation of hydrogen isotopes [J]. ACS Applied Materials & Interfaces, 2022, 14 (6): 7826-7835.) relates to a hydrophobic catalyst using cordierite as a carrier, which discloses that the cordierite surface is grafted with an organic polymer having intrinsic hydrophobicity. The grafting process is relatively cumbersome, and the hydrophobicity provided by the organic polymer is poor. CN107930621A discloses a hydrophobic catalyst with foamed silicon carbide as a carrier, wherein PTFE is first applied to foamed SiC by an impregnation method, and then the active component Pt is loaded, but PTFE is a hydrophobic substance, which is unfavorable for the dispersion of Pt, and thus is unfavorable for the activity of the catalyst. In addition, foamed SiC and cordierite are both ceramic materials, with heavy weight, poor processability, and easy powdering. CN104226311A relates to a hydrophobic catalyst with foamed nickel as a carrier, wherein the active component Pt is first loaded on porous carbon to make Pt / C, then Pt / C is mixed with PTFE and Triton to make an emulsion, and finally Pt / C / PTFE is loaded on foamed nickel by impregnation to obtain a hydrophobic catalyst. The preparation method is simple, and foamed nickel has the advantages of strong processability and strong mass transfer and heat transfer capacity, but Pt is easily covered by PTFE, resulting in a low utilization rate of Pt, which is unfavorable for the progress of catalytic reaction. Therefore, there is still a need to continue to develop regular hydrophobic catalysts with excellent performance.

[0049] Based on this, the present application provides a hydrophobic catalyst and a preparation method thereof. The present application and optional implementation methods are described in more detail below.

[0050] Preparation method of hydrophobic catalyst

[0051] The present application provides a method for preparing a hydrophobic catalyst, comprising: S1, attaching a carbon-containing suspension to a metal skeleton and then drying it to load carbon onto the metal skeleton to obtain a composite carrier, wherein the carbon-containing suspension comprises powdered carbon and a dispersant dispersed in a silica sol; S2, loading an active metal onto the composite carrier to obtain an original catalyst; and S3, treating the original catalyst with a modified solution to obtain the hydrophobic catalyst, wherein the modified solution comprises a hydrophobic silane and an organic solvent.

[0052] The present invention adopts a layer-by-layer loading method, wherein powdered carbon is first loaded onto a metal skeleton through silica sol, and the obtained composite carrier has an increased specific surface area, which is beneficial to the subsequent loading of active substances; the active metal is further loaded, and compared with the method in which carbon powder of the active metal is directly attached to the metal skeleton through polytetrafluoroethylene having a bonding effect, in which part of the active metal is covered by polytetrafluoroethylene, the present invention avoids the active metal from being covered and increases the exposure of the active metal; and after the active metal is loaded, a hydrophobic modification is performed through a modification solution including hydrophobic silane, which achieves the hydrophobic modification while also avoiding the active metal from being covered, thereby facilitating the improvement of the utilization rate of the active metal and the improvement of the catalytic activity of the hydrophobic catalyst.

[0053] According to some embodiments, the material of the metal skeleton is any one of nickel, iron, cobalt, copper, magnesium, aluminum, and stainless steel. Therefore, it is helpful to select the metal skeleton according to the actual purpose to meet the requirements of corrosion resistance, cost, etc. Preferably, the material of the metal skeleton is nickel.

[0054] According to some embodiments, the metal skeleton is in the form of any one of foam, wire mesh, fiber, and honeycomb. This is beneficial for regulating the resistance of the fluid passing through the catalyst, and increases the specific surface area of ​​the metal skeleton, which is beneficial for the subsequent loading of active substances. Preferably, the metal skeleton is in the form of foam.

[0055] According to some embodiments, relative to the total mass of the carbon-containing suspension, the mass percentage of the powdered carbon is 1% to 5%, the mass percentage of the dispersant is 0.5% to 3%, and the mass percentage of silicon dioxide in the silica sol relative to the silica sol is 20% to 40%. This is conducive to forming a stable carbon-containing suspension and achieving uniform adhesion. Exemplarily, relative to the total mass of the carbon-containing suspension, the mass percentage of the powdered carbon is 1%, 2%, 3%, 4%, 5% or a value between the ranges consisting of any two values, but is not limited thereto. Exemplarily, relative to the total mass of the carbon-containing suspension, the mass percentage of the dispersant is 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a value between the ranges consisting of any two values, but is not limited thereto. Illustratively, the mass percentage of silicon dioxide in the silica sol relative to the silica sol is 20%, 25%, 30%, 35%, 40% or a value between any two values, but is not limited thereto.

[0056] According to some embodiments, the powdered carbon is selected from one or more of activated carbon, graphite powder, carbon nanotubes, and carbon black, thereby facilitating the increase of the specific surface area of ​​the metal skeleton.

[0057] According to some embodiments, the average particle size of the powdered carbon is 10nm to 100nm. This is beneficial to increase the specific surface area of ​​the metal skeleton. Exemplarily, the average particle size of the powdered carbon is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or a value between the ranges consisting of any two values, but is not limited thereto.

[0058] According to some embodiments, the dispersant is Triton X-100, which is beneficial to the stability of the carbonaceous suspension and the formation of a more uniformly dispersed attachment on the metal skeleton.

[0059] According to some embodiments, in S1, the drying temperature is 100°C to 120°C and the drying time is 1 hour to 3 hours, which is conducive to the volatilization of water in the silica sol and the silica particles play a bonding role.

[0060] According to some embodiments, the mass ratio of the composite carrier to the metal skeleton is (1.2-1.8): 1. Exemplarily, the mass ratio of the composite carrier to the metal skeleton is 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.7: 1, 1.8: 1 or a value between the ranges formed by any two values, but not limited thereto. Thus, it is beneficial to increase the specific surface area of ​​the metal skeleton, increase the sites for subsequent loading of active substances, and improve the dispersibility of the active substances.

[0061] According to some embodiments, before S2, the preparation method further includes loading a nickel cobaltate precursor onto the composite support by a hydrothermal method; and calcining the composite support loaded with the nickel cobaltate precursor to obtain a composite support loaded with nickel cobaltate (NiCo2O4), wherein loading the nickel cobaltate precursor onto the first support by a hydrothermal method includes reacting an aqueous mixture including a nickel source and a cobalt source, the composite support, a surfactant and a nucleating agent in a hydrothermal reactor, wherein the molar ratio of the cobalt element in the cobalt source to the nickel element in the nickel source is 2:1. The nickel cobaltate can further improve the specific surface area and roughness of the support, which is beneficial to increase the attachment sites for loading active metals in S2, and the nickel cobaltate contains abundant hydroxyl groups, which is beneficial to react with hydrophobic silanes in S3, further improving hydrophobicity. Exemplarily, the cobalt source is a cobalt salt such as cobalt acetate, cobalt chloride, cobalt nitrate and its hydrate, but is not limited thereto. Exemplarily, the nickel source is a nickel salt such as nickel acetate, nickel chloride, nickel nitrate and its hydrate, but is not limited thereto.

[0062] According to some embodiments, the temperature of the hydrothermal reaction is 110° C. to 130° C., and the time is 5 h to 8 h. This is conducive to the full progress of the hydrothermal reaction and the formation of a nickel cobalt oxide precursor on the composite support.

[0063] According to some embodiments, the amount of the cobalt element in the cobalt source is 0.1 mmol to 1 mmol per gram of the composite support. For example, the amount of the cobalt element in the cobalt source is 0.1 mmol, 0.2 mmol, 0.4 mmol, 0.6 mmol, 0.8 mmol, 0.10 mmol or a value between any two values ​​per gram of the composite support, but is not limited thereto.

[0064] According to some embodiments, the concentration of the ions containing the cobalt element in the cobalt source is 0.01 mol / L to 0.1 mol / L relative to the aqueous mixture. Exemplarily, the concentration of the ions containing the cobalt element in the nickel cobaltate precursor is 0.01 mol / L, 0.02 mol / L, 0.40 mol / L, 0.06 mol / L, 0.08 mol / L, 0.10 mol / L or a value between any two values, but not limited thereto.

[0065] According to some embodiments, the calcination temperature is 300° C. to 450° C. and the calcination time is 2.5 h to 4.5 h, which is beneficial for converting the nickel cobalt oxide precursor into nickel cobalt oxide.

[0066] According to some embodiments, the surfactant is cetyltrimethylammonium bromide.

[0067] According to some embodiments, the nucleating agent is urea.

[0068] According to some embodiments, the concentration of the surfactant is 0.005 mol / L to 0.04 mol / L, and the concentration of the nucleating agent is 0.02 mol / L to 0.20 mol / L, relative to the aqueous mixture. Exemplarily, the concentration of the surfactant is 0.005 mol / L, 0.010 mol / L, 0.015 mol / L, 0.020 mol / L, 0.025 mol / L, 0.030 mol / L, 0.035 mol / L, 0.040 mol / L, or a value between any two values, but not limited thereto. Exemplarily, relative to the aqueous mixture, the concentration of the nucleating agent is 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.08 mol / L, 0.10 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, 0.20 mol / L or a value between the ranges consisting of any two values, but is not limited to these.

[0069] According to some embodiments, in S2, loading the active metal onto the composite carrier includes immersing the composite carrier in a solution including ions containing active metal elements, and volatilizing the solvent in the solution including ions containing active metal elements to obtain a carrier loaded with an active metal precursor, wherein the active metal is selected from one or more of Pt, Pd, Ru, Rh, Ir, Fe, Fe-doped Pt, Ru-doped Pt, and Ir-doped Pt; and performing a reduction treatment on the carrier loaded with the active metal precursor to obtain an original catalyst, wherein the reduction treatment includes reducing the carrier loaded with the active metal precursor in an atmosphere containing a reducing gas. The above-mentioned impregnation process utilizes a uniform solution including ions containing active metal elements, which is conducive to the attachment of metal ions to the composite carrier. The above-mentioned reduction process using a reducing gas is conducive to sufficient reduction to obtain the active metal.

[0070] According to some embodiments, the solvent of the solution comprising ions containing active metal elements is selected from one or more of ethanol, methanol, water, ethylene glycol, and acetone.

[0071] According to some embodiments, the reducing gas is hydrogen.

[0072] According to some embodiments, the content of the active metal element in the solution comprising ions containing active metal elements is 3g / L to 10g / L. Thus, it is beneficial to improve the catalytic efficiency of the hydrophobic catalyst and has good cost-effectiveness. Exemplarily, the content of the active metal element in the solution comprising ions containing active metal elements is 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L or a value between the ranges consisting of any two values, but is not limited thereto.

[0073] According to some embodiments, the ratio of the mass of the composite carrier to the volume of the solution comprising ions containing active metal elements is 0.1 g / mL to 1.0 g / mL. Exemplarily, the ratio of the mass of the composite carrier to the volume of the solution comprising ions containing active metal elements is 0.1 g / mL, 0.3 g / mL, 0.5 g / mL, 0.7 g / mL, 1.0 g / mL or a value between any two values, but not limited thereto.

[0074] The present disclosure has no particular limitation on treating the original catalyst with a modification solution, and those skilled in the art may perform the treatment according to methods known in the art.

[0075] According to some embodiments, treating the original catalyst with the modifying solution includes drying the original catalyst after the modifying solution is attached to the original catalyst. Exemplarily, the original catalyst is immersed in the modifying solution, then removed and dried. This is conducive to simplifying the process and allowing the original catalyst to fully contact with the modifying solution, thereby facilitating the improvement of hydrophobicity.

[0076] According to some embodiments, in the modification solution, the organic solvent is ethanol.

[0077] According to some embodiments, the hydrophobic silane comprises a structural formula of R n SiR' m Silane, n is 1, 2 or 3, m=4-n, R is a C1-C20 alkyl substituted with fluorine, and R' is a C1-C4 alkoxy. According to some embodiments, R has x carbon atoms, and R is substituted with 2x-9 to 2x+1 fluorine atoms. This is more conducive to improving hydrophobicity.

[0078] According to some embodiments, the hydrophobic silane includes one or more of heptadecafluorodecyltrimethoxysilane (FD-TMS), perfluorodecyltriethoxysilane, and tridecafluorooctyltriethoxysilane.

[0079] According to some embodiments, in the modified solution, the mass percentage of the hydrophobic silane is 0.1% to 0.5%. This is conducive to better dispersion of the hydrophobic silane in the organic solvent, so that it is evenly attached to the original catalyst. Exemplarily, in the modified solution, the mass percentage of the hydrophobic silane is 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or a value between the ranges consisting of any two values, but is not limited thereto.

[0080] Hydrophobic Catalyst

[0081] The second aspect of the present application provides a hydrophobic catalyst obtained according to the preparation method of any of the above embodiments. The hydrophobic catalyst has improved catalytic activity and the above other advantages.

[0082] Example

[0083] Below, the embodiment of the application is described. The embodiment described below is exemplary, is only used to explain the application, and cannot be construed as limiting the application. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the document in this area or the product specification are carried out. All reagents or instruments that do not indicate the manufacturer are conventional products that can be obtained by commercial purchase.

[0084] Example 1

[0085] Loaded Carbon

[0086] 2 g of silica sol (purchased from Shanghai McLean Biochemical Technology Co., Ltd., with a solid content of 29% to 31%), 0.5 mL of Triton X-100, 1 g of activated carbon (purchased from Fuzhou Yihuan Carbon Co., Ltd., with an average particle size of 30 nm to 80 nm) and 30 mL of deionized water are mixed under magnetic stirring to prepare a carbon-containing suspension, in which the mass percentage of the powdered carbon is 3% relative to the total mass of the carbon-containing suspension.

[0087] 0.26 g of nickel foam (purchased from the manufacturer, Kunshan Zhangpu Town Baiyida Electronic New Materials Business Department, round cake shape, bottom diameter of 27 mm, thickness of 2 mm, porosity of 75 ppi, and specific surface area of ​​1 m 2 / g) was immersed in the above carbon-containing suspension, taken out and placed in an oven at 100°C for drying for 1h, and the above process was repeated until the mass ratio of the dried product to the initial nickel foam was 1.5:1, to obtain 0.385g of a composite carrier.

[0088] Loaded Nickel Cobalt Oxide

[0089] Under magnetic stirring, 2mmol Co(NO3)2·6H2O, 1mmol NiCl2·6H2O, 0.8mmol hexadecyltrimethylammonium bromide (CTAB) and 3.6mmol urea were dissolved in 40mL deionized water, and the above solution and 10 pieces of the above composite carrier (3.85g in total) were transferred to a Teflon-lined reactor, and then placed in an oven and reacted at 120°C for 6h. After the reaction, the nickel foam was fished out, washed with deionized water and ethanol respectively, dried and placed in a muffle furnace, and calcined at 350°C for 3h to obtain 10 pieces of NiCo2O4-loaded composite carriers (4.07g in total), wherein the mass percentage of NiCo2O4 was 5%.

[0090] Load Pt

[0091] At room temperature, a piece of 0.407g of the above-mentioned composite support loaded with NiCo2O4 was immersed in 1.5mL of 0.03mol / L ethanol solution of hexahydrate chloroplatinic acid (H2PtCl6·6H2O). After the ethanol was completely volatilized, it was placed in an oven for drying at 60°C for 12h, and then placed in a tubular furnace, and heated from room temperature to 220°C at a rate of 10°C / min under N2 atmosphere (flow rate of 500mL / min). After reaching this temperature, H2 (flow rate of 500mL / min) was introduced for reduction, and the reduction was carried out at 220°C for 8h. After the reduction was completed, the introduction of H2 was stopped, and the catalyst was cooled overnight under the protection of N2 (flow rate of 500mL / min), and 0.410g of the original catalyst was obtained.

[0092] Hydrophobic treatment

[0093] The original catalyst was immersed in 5 mL of 0.2 wt % ethanol solution of heptadecafluorodecyltrimethoxysilane (FD-TMS) for 24 h, fished out and dried at 80° C. overnight to obtain 0.412 g of a hydrophobic catalyst.

[0094] Specific surface area test

[0095] The adsorption and desorption isotherms of the composite support and the composite support loaded with NiCo2O4 were measured by nitrogen adsorption using a surface area and porosity analyzer (ASAP 2460 from Micromeritics, USA). The specific surface area of ​​the composite support was calculated using the BET (Brunauer Emmett Teller) method. The specific surface area of ​​the composite support was 52 m 2 / g, the specific surface area of ​​the composite carrier loaded with NiCo2O4 is 123m 2 / g. It can be seen that compared with the specific surface area of ​​1m 2 / g of raw material foam nickel, the loading of activated carbon significantly increased the specific surface area of ​​the foam nickel substrate and provided more sites for the subsequent growth of NiCo2O4; the loading of NiCo2O4 further significantly increased the specific surface area and roughness, thereby increasing the sites for loading metal Pt.

[0096] Example 2

[0097] The hydrophobic catalyst was prepared in the same manner as in Example 1, except that the step of loading NiCo2O4 was not performed.

[0098] Comparative Example 1

[0099] The hydrophobic catalyst was prepared in the same manner as in Example 1, except that the carbon loading step was not performed.

[0100] Comparative Example 2

[0101] The hydrophobic catalyst was prepared in the same manner as in Example 1, except that the carbon loading was carried out by hydrothermal carbonization, using glucose as the carbon source, growing C on nickel foam, and combining with activation treatment. The specific experimental steps of the above carbon loading method are as follows:

[0102] (1) Loading C: 10 pieces of 0.27g round cake-shaped nickel foam (2.70g in total) were placed in deionized water and ethanol solution and ultrasonically cleaned for 20 minutes to remove surface impurities. Under magnetic stirring, 4g of d-glucose was added to a beaker containing 30mL of deionized water, and then the solution and the above 10 pieces of nickel foam were placed in a 50mL Teflon-lined reactor. The reactor was placed in an oven and reacted at 180°C for 8h. After the reaction, the nickel foam was fished out and washed with deionized water several times, and then placed in an oven to dry, to obtain 10 pieces of nickel foam with carbon (C) on the surface (3.00g in total, 0.3g per piece), and the mass of C loaded on the surface of each piece of nickel foam was 0.03g.

[0103] (2) Use KOH to activate the carbon loaded on the surface of the dried nickel foam: prepare a 0.01 g / mL KOH solution according to the mass ratio of C to KOH of 1:2, mix the two and put them into an oven, react at 120°C for 12 hours, then put the obtained nickel foam into a tubular furnace and activate it in a nitrogen (N2) atmosphere by heating from room temperature to 700°C at a heating rate of 5°C / min and keeping it at 700°C for 1 hour. After the activation, wash the nickel foam with deionized water and finally put it into a vacuum oven and dry it at 150°C for 24 hours to obtain a porous carbon loaded nickel foam with a specific surface area of ​​26 m 2 / g, which is significantly lower than the specific surface area of ​​the composite carrier in Example 1.

[0104] Morphology of hydrophobic catalysts

[0105] The hydrophobic catalyst of Example 1 was observed by a Sigma 300 scanning electron microscope of the German ZEISS company. Figure 1 As shown, the load on the metal skeleton is evenly distributed and dispersed without agglomeration.

[0106] Contact angle test

[0107] The surface of the hydrophobic catalysts in the above examples and comparative examples was tested using a SDC-350 contact angle measuring instrument from Dongguan Dingsheng Instrument Co., Ltd., China. A drop of deionized water was dripped onto the surface to be tested, and the contact angle of the drop was read. The contact angle test graph of the hydrophobic catalyst in Example 1 is shown in FIG. Figure 2 As shown, the contact angle is as high as 161.2°, achieving superhydrophobic performance.

[0108] Catalytic activity test

[0109] The catalytic activity of the above hydrophobic catalysts was tested using a parallel flow hydrogen isotope liquid phase catalytic exchange device. Before the catalytic reaction started, constant temperature water at 60°C was introduced into the device to preheat the catalytic column (equipped with 23mL of the above hydrophobic catalyst) and the packing column, and then N2 was introduced to purge the air in the device. H2 was introduced from the bottom of the water vapor saturator at a flow rate of 0.5L / min, and the water vapor saturated with light and heavy water at a temperature of 60°C was brought into the catalytic column. A water-hydrogen exchange reaction occurred on the hydrophobic catalyst, and the deuterium abundance of the gas sample at the inlet and outlet of the catalytic column was measured by a mass spectrometer (Thermofisher, MAT253). The deuterium density of the water sample was measured by a densitometer for the gas condensate after the reaction. The catalytic exchange efficiency η and the total volume mass transfer coefficient Kya were calculated by the following formula.

[0110]

[0111] Where X represents the percentage of deuterium atoms in the gas condensate after the isotope exchange reaction; Y0 represents the percentage of deuterium atoms at the inlet of the catalytic column, and Y t represents the percentage of deuterium atoms at the outlet of the catalytic column; Y* is the percentage of deuterium atoms in the inlet and outlet gases of the catalytic column when equilibrium is reached; α represents the separation coefficient of hydrogen-deuterium phase exchange, which is 1.046 at 60°C; G is the gas flow rate (m 3 / s), V is the volume of the catalyst bed (m 3 The curves of the total volume mass transfer coefficient Kya of the above-mentioned Examples 1 to 2 and Comparative Example 1 relative to the gas velocity are as follows: Figure 3 shown.

[0112] The contact angles of the hydrophobic catalysts prepared in Examples 1 to 2 and Comparative Examples 1 to 2 and the total volume mass transfer coefficients Kya at a gas velocity of 0.5 L / min are shown in Table 1 below.

[0113] Table 1

[0114]

[0115]

[0116] Among them, “ / ” means that no corresponding performance test data is made.

[0117] The above results show that according to the scheme of the present invention, powdered carbon, active metal and hydrophobic silane are loaded layer by layer on the metal skeleton, which can improve the utilization rate of active metal while achieving hydrophobic modification. Compared with the carbon layer of comparative example 1 without silica sol loading and the carbon layer loaded by hydrothermal carbonization method in comparative example 2, the catalytic activity of the hydrophobic catalyst is significantly improved in Examples 1 and 2 of the present disclosure, and the total volume mass transfer coefficient reaches 15×10 -2 s -1 In particular, loading nickel cobaltate after loading powdered carbon and before loading active metal can further improve hydrophobicity and catalytic activity.

[0118] The above descriptions are only some specific embodiments of the present disclosure, which are intended to illustrate the present disclosure and are not intended to limit the scope of protection claimed in the present application. All modifications, substitutions, or direct / indirect applications made in other related technical fields based on the inventive concept of the present disclosure and using the description of the present application are included in the scope of protection claimed in the present application.

Claims

1. A method for preparing a hydrophobic catalyst, comprising: S1, by attaching a carbon-containing suspension to a metal skeleton and then drying it to load carbon onto the metal skeleton to obtain a composite carrier, wherein the carbon-containing suspension includes powdered carbon dispersed in silica sol and a dispersant; S2, loading the active metal onto the composite carrier to obtain an original catalyst; and S3, treating the original catalyst with a modification solution to obtain the hydrophobic catalyst, wherein the modification solution comprises hydrophobic silane and an organic solvent.

2. The preparation method according to claim 1, characterized in that: The material of the metal skeleton is any one of nickel, iron, cobalt, copper, magnesium, aluminum, and stainless steel; preferably, the shape of the metal skeleton is selected from any one of foam, wire mesh, fiber, and honeycomb.

3. The preparation method according to claim 1, characterized in that: Relative to the total mass of the carbon-containing suspension, the mass percentage of the powdered carbon is 1% to 5%, the mass percentage of the dispersant is 0.5% to 3%, and the mass percentage of silicon dioxide in the silica sol relative to the silica sol is 20% to 40%; preferably, the powdered carbon is selected from one or more of activated carbon, graphite powder, carbon nanotubes, and carbon black; preferably, the average particle size of the powdered carbon is 10nm to 100nm; preferably, the dispersant is Triton X-100.

4. The preparation method according to claim 1, characterized in that: In S1, the drying temperature is 100°C to 120°C, and the drying time is 1h to 3h; preferably, the mass ratio of the composite carrier to the metal skeleton is (1.2 to 1.8):

1.

5. The preparation method according to claim 1, characterized in that: In S2, loading the active metal onto the composite support comprises: The composite carrier is immersed in a solution including ions containing active metal elements, and the solvent in the solution including ions containing active metal elements is volatilized to obtain a carrier loaded with an active metal precursor, wherein the active metal is selected from one or more of Pt, Pd, Ru, Rh, Ir, Fe, Fe-doped Pt, Ru-doped Pt, and Ir-doped Pt. Preferably, the solvent of the solution including ions containing active metal elements is selected from one or more of ethanol, methanol, water, ethylene glycol, and acetone; and The carrier loaded with the active metal precursor is subjected to a reduction treatment to obtain an original catalyst, wherein the reduction treatment comprises reducing the carrier loaded with the active metal precursor in an atmosphere containing a reducing gas, preferably, the reducing gas is hydrogen.

6. The preparation method according to claim 5, characterized in that: The content of the active metal element in the solution comprising ions containing the active metal element is 3 g / L to 10 g / L; preferably, the ratio of the mass of the composite carrier to the volume of the solution comprising ions containing the active metal element is 0.1 g / mL to 1.0 g / mL.

7. The preparation method according to claim 1, characterized in that: In S3, treating the original catalyst with a modification solution comprises drying the modified solution after adhering to the original catalyst; preferably, in the modified solution, the organic solvent is ethanol; preferably, the hydrophobic silane comprises a structural formula of R n SiR' m Silane, n is 1, 2 or 3, m=4-n, R is a C1-C20 alkyl group substituted by fluorine, and R' is a C1-C4 alkoxy group; preferably, based on R having x carbon atoms, R is substituted with 2x-9 to 2x+1 fluorine atoms.

8. The preparation method according to claim 1, characterized in that: In the modified solution, the mass percentage of the hydrophobic silane is 0.1% to 0.5%.

9. The preparation method according to claim 1, characterized in that: Before S2, the preparation method further comprises: Loading the nickel cobalt oxide precursor onto the composite support by a hydrothermal method; and calcining the composite support loaded with nickel cobalt oxide precursor to obtain a composite support loaded with nickel cobalt oxide, Wherein, loading the nickel cobaltate precursor onto the first carrier by a hydrothermal method comprises reacting an aqueous mixture comprising a cobalt source, a nickel source, the composite carrier, a surfactant and a nucleating agent in a hydrothermal reactor, wherein the molar ratio of the cobalt element in the cobalt source to the nickel element in the nickel source is 2:1; preferably, the temperature of the hydrothermal reaction is 110°C to 130°C, and the time is 5h to 8h; preferably, the amount of the cobalt element in the cobalt source is 0.1mmol to 1mmol per gram of the composite carrier; preferably, relative to the hydrothermal reaction, the amount of the cobalt element in the cobalt source is 0.1mmol to 1mmol. Preferably, the concentration of the ions containing the cobalt element in the cobalt source is 0.01mol / L to 0.1mol / L; preferably, the calcination temperature is 300°C to 450°C, and the time is 2.5h to 4.5h; preferably, the surfactant is hexadecyltrimethylammonium bromide; preferably, the nucleating agent is urea; preferably, relative to the aqueous mixture, the concentration of the surfactant is 0.005mol / L to 0.04mol / L, and the concentration of the nucleating agent is 0.02mol / L to 0.20mol / L.

10. A hydrophobic catalyst obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of neat hydrophobic catalyst

    CN104226311A

  • Silicon carbide hydrophobic catalyst and preparation method

    CN107930621A

  • Preparation method of hydrophobic catalyst for hydrogen-water isotope exchange

    CN103551202A

  • Metal oxide supported noble metal catalyst, and preparation method and use thereof

    CN108452797A

  • Foamed nickel-loaded iron-cobalt-nickel metal nano-catalyst and preparation method and application thereof

    CN111495417A